Presentation of the 1/5 questions on the vector of mobility concept in the case of research on emigrant tourism - Verbič Koprivšek, Maruša (Journal for Geography, 2017)
The paper presents the 1/5 questions on the vector of mobility research concept. The concept is applicable to an interdisciplinary study of all types of spatial mobility of population, for different purposes and at different levels of complexity. The use of the concept is practically presented through the example of research on emigrant tourism, which is also defined for the first time in this article. With the 1/5 questions on the vector of mobility concept the emigrant tourism of Slovene emigrants from Denver, Colorado, has been studied, with usage of the data obtained on the basis of historical sources and literature, especially the emigrant newspapers or official organs of some Slovene fraternal benefit associations in the United States, as well as field research.
Keywords: 1/5 questions on the vector of mobility concept; emigrant tourism; population mobility; tourism; migration; Slovene emigrants in the U.S.